Preoperative experience for public hospital patients with gynecologic cancer: Do structural barriers widen the gap? - Frey, Melissa K.; Moss, Haley A.; Musa, Fernanda; Rolnitzky, Linda; David‐West, Gizelka; Chern, Jing‐Yi; Boyd, Leslie R.; Curtin, John P. (Cancer, 2016)
BACKGROUND Widespread disparities in care have been documented in women with gynecologic cancer in the United States. This study was designed to determine whether structural barriers to optimal care were present during the preoperative period for patients with gynecologic cancer. METHODS A retrospective review was conducted for patients undergoing surgery for a gynecologic malignancy at a public hospital or a private hospital staffed by the same team of gynecologic oncologists between July 1, 2013 and July 1, 2014. RESULTS Two hundred fifty‐seven cases were included for analysis (public hospital, 69; private hospital, 188). Patients treated at the private hospital were older (58 vs 52 years; P = .004) and had similar medical comorbidities (median Charlson comorbidity index at both hospitals, 6) but required fewer hospital visits in preparation for surgery (2 vs 4; P < .001). Public hospital patients had a longer wait time from the diagnosis of disease to surgery (63 vs 34 days; P < .001). According to a multiple linear regression model, the public hospital setting was associated with a longer interval from diagnosis to surgery with adjustments for the insurance status, age at diagnosis, cancer stage, and number of preoperative hospital visits (P < .001). CONCLUSIONS Patients at the public hospital were subject to a greater number of preoperative visits and had to wait longer for surgery than patients at the private hospital. Attempts to reduce health care disparities should focus on improving efficiency in health care delivery systems once contact has been established. Cancer 2016;122:859–67. © 2016 American Cancer Society. Health care disparities are present during the preoperative window for women with gynecologic cancer. Patients at a public hospital are subject to a greater number of preoperative visits and have to wait longer for surgery than patients at a private hospital.